Laser‐Assisted Fabrication of Injectable Nanofibrous Cell Carriers. Issue 2 (21st November 2021) - Nakielski, Paweł; Rinoldi, Chiara; Pruchniewski, Michał; Pawłowska, Sylwia; Gazińska, Małgorzata; Strojny, Barbara; Rybak, Daniel; Jezierska‐Woźniak, Katarzyna; Urbanek, Olga; Denis, Piotr; Sinderewicz, Emilia; Czelejewska, Wioleta; et al.
Abstract: The use of injectable biomaterials for cell delivery is a rapidly expanding field which may revolutionize the medical treatments by making them less invasive. However, creating desirable cell carriers poses significant challenges to the clinical implementation of cell‐based therapeutics. At the same time, no method has been developed to produce injectable microscaffolds (MSs) from electrospun materials. Here the fabrication of injectable electrospun nanofibers is reported on, which retain their fibrous structure to mimic the extracellular matrix. The laser‐assisted micro‐scaffold fabrication has produced tens of thousands of MSs in a short time. An efficient attachment of cells to the surface and their proliferation is observed, creating cell‐populated MSs. The cytocompatibility assays proved their biocompatibility, safety, and potential as cell carriers. Ex vivo results with the use of bone and cartilage tissues proved that NaOH hydrolyzed and chitosan functionalized MSs are compatible with living tissues and readily populated with cells. Injectability studies of MSs showed a high injectability rate, while at the same time, the force needed to eject the load is no higher than 25 N. In the future, the produced MSs may be studied more in‐depth as cell carriers in minimally invasive cell therapies and 3D bioprinting applications. Abstract : The proposed laser‐assisted microscaffold (MSs) fabrication can effectively produce thousands of identical MSs, leading to the development of injectable electrospun nanofibers. The efficient cell attachment on the MSs surface creates agglomerations of cell‐populated MSs, while MSs suspended in hyaluronic acid can be efficiently injected through a 26G needle by applying an ejecting force suitable for manual injection.